Digital video composition for production value enrichment in ivml using heutagogy approach - Nur Faraha Hj. Mohd. Naim (2020)
The research focuses on the constructive significance of digital video compositing embedded with heutagogy Teaching and Learning (T&L) quality on Affective and Cognitive Value. The ideality of interactive within one single video timeline as heutagogy approach was infused in Interactive Video Mobile Learning (IVML) development by embedding the cue points feature. There are issues and challenges that arise together with the progressive practice of interactive digital video compositing in education such as insufficient T&L quality approach in educational videos, the importance of visual aesthetics, the significance of video length, uncertain measurement proxy to measure the video engagement, and scant publications on interactive videos. Hence an opening move was crafted for better comprehension of IVML prospect in production value. The IVML prototype was developed for interactive digital video compositing production style embedded with heutagogy approach to stimulate the affective value and leverage the cognitive value of learners. This research has conducted an experiment with the heutagogy quality infusion in an educational video, investigated the correlation between affective and cognitive values, assessed the importance of visual aesthetics in educational videos, and measured the relationship strength between engagement and encouragement to achieve the research objectives. There are six analytical techniques and several design frameworks models have been developed in this research to determine the results and research findings. The results show that the IVML production style indeed manages to stimulate the affective value and leverage the cognitive value however, the relationship between the affective and cognitive is weak indicating that their positive feelings toward the production style have no influence on their mental cognition in processing the information delivered. The outcomes derived from this study are significant to the production value enrichment on educational video wherein, the results have opened a new direction of IVML prospect in video-based learning.